Bias Gender dalam Novel La Grande Borne Karya NH. Dini - Dilla, Raili Irfa; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this article was to describe the gender diffraction in novel La Grande Borne by Nh. Dini, evaluated from five aspects, (a) marginalization, (b) subordination, (c) stereotype, (d) violence, and (e) double work load. The data of this study was the sentences that refer to the gender diffraction.. The analyze technics were (1) describe the data, (2) analyze the data that refer to gender, (3) lnterpretated the unfair in gender, and (4) conclusion. The results of this study could be concluded that the women main character get the unfair gender. The unfairy of gender that had happened was the gender (a) marginalization, (b) woman subordination, (c) the woman stereotype, (d) the women violence,(e)double work load.